Training of pupils for olympiads in informatics as a mean of choice of future professional activity in the field of information technology - Kuzmenko, Alla (ScienceRise: Pedagogical Education, 2017)
In the connection with the development of information-communicative technologies, informatics teachers face the question as to the new content of the study, new means, methods of the study, based on pupils’ independent research, creative learning activity. Alongside with the modern technologies development, leading universities introduce learning directions as to the study of databases, Big Data, Internet of Things, Machine Learning, cloud technologies; web-additions developing; mobile devices programming. These themes are not studied in learning programs for a secondary educational institution that influences the insufficient readiness of senior pupils. Olympiads in informatics, office technologies, web-design, computer graphics, computed animation take place annually in city Kyiv. Schoolchildren of 6–11classes take part in them. The number of prize winners of the Olympiad “web-design” among pupils of the Technical lyceum of city Kyiv annually grows that is the result of the system training of talented children. At training for the Olympiad in web-design teachers of informatics of the Technical lyceum of city Kyiv started the work on the course “Internet technologies”, consisted of bases of the work with HTML, CSS and Java Script using LCMS MOODLE. Just a teacher of a secondary educational institution may give pupils understanding of different direction of IT field, create conditions for the complete realization of their creative potential, inclinations, abilities, satisfaction of needs and learning-cognitive demands. Having certain knowledge in different IT directions, received at training for Olympiads in informatics, pupils may choose their future profession more consciously